Estimation of the CH4 emission factors for the three most representative municipal wastewater treatment processes in Mexico. - Paredes Figueroa, María Guadalupe (My University, 2016)
Emission factors; methane emission; wastewater treatment.
Keywords: Emission factors; methane emission; wastewater treatment.